Immune-related mechanisms and immunotherapy in extragonadal germ cell tumors - Xiu, Weigang; Pang, Jiyun; Hu, Yang; Shi, Huashan (Frontiers in Immunology, 2023)
Extragonadal germ cell tumors (EGCTs) are relatively rare tumors, accounting for 1%–5% of all GCTs. Their histological origin is related to a gonadal origin, but they are located outside the gonad. They show great variation in morphology and can occur in the cranium, mediastinum, sacrococcygeal bone, and other areas. The pathogenesis of EGCTs is poorly understood, and their differential diagnosis is extensive and challenging. EGCT behavior varies greatly according to patient age, histological subtype, and clinical stage. In this review, we summarize the current research progress regarding the pathogenesis, diagnosis, and treatment of EGCTs from an immunology perspective.